Assessing the Psychometric Properties of Both a Global and a Domain-Specific Perceived Quality of Life Measure When Used with Youth Who Have Chronic Conditions - McDougall, Janette (Soc Indic Res, 2012)
The purpose of this paper was to assess the psychometric properties of the Students’ Life Satisfaction Scale (SLSS) and the Brief Multidimensional Students’ Life Satisfaction Scale (BMSLSS) when used with youth who have chronic conditions. Baseline data from a longitudinal study examining predictors of changes in perceived quality of life (PQOL) for youth with chronic conditions were used. SLSS and BMSLSS data were collected on over 400 youth aged 11–17 using youth self-report and parent proxy-report versions. Internal consistency, convergent validity, and factor structure were examined for both versions. Extent of agreement and magnitude of differences between youth and parent report were evaluated. Finally, gender, age, and condition group differences in youth report scores were examined for the SLSS and BMSLSS. Strong internal consistency was demonstrated for the youth and parent reports of both measures. As with normative samples, a single factor structure was found for youth and parent reports of the BMSLSS. However, both youth and parent reports of the SLSS had a two-factor structure: one consisting of five positively worded items, and the other, two negatively worded items. Youth reported their PQOL to be significantly higher than did their parents. Significant differences in PQOL scores for the youth report were not found by age, gender, or conditions. Findings show that, from a psychometric standpoint, the BMSLSS (both youth and parent report) is a promising measure of PQOL for use in population-based research with youth who have chronic conditions. The SLSS may need to be revised to exclude negative items when used with this population of youth.